(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The article examines the genre of detective novel modifications for children and young Ukrainian writers of the late XX – early XXI centuries, their characteristics, the main objects of the image. To focus on signs of a detective for young readers, copyright innovation, especially considering relevant topics and issues, specifics of reception.